2022
DOI: 10.1186/s12891-022-06097-9
|View full text |Cite
|
Sign up to set email alerts
|

High reliability and accuracy of dynamic magnetic resonance imaging in the diagnosis of cervical Spondylotic myelopathy: a multicenter study

Abstract: Background Cervical spondylotic myelopathy (CSM) is a critical condition that results in significant neurologic deterioration. An accurate diagnosis is essential for determining its outcome and prognosis. The pathology is strongly associated with dynamic factors; therefore, dynamic magnetic resonance (MR) image could be crucial to accurately detect CSM. However, very few studies have evaluated the reliability and accuracy of dynamic MR in CSM. In this study, we aimed to compare intra- and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Extension of the neck position has lower FA values than exion of the neck and natural position. It has been previously reported that hyperextension sagittal MRI produces more excellent intra-observer reliability than neutral sagittal MRI [20] . The above may be the mechanism by which the FA value in the extension neck position best assesses the value of postoperative recovery in patients with CSM, and the detailed mechanism is unknown.…”
Section: Discussionmentioning
confidence: 95%
“…Extension of the neck position has lower FA values than exion of the neck and natural position. It has been previously reported that hyperextension sagittal MRI produces more excellent intra-observer reliability than neutral sagittal MRI [20] . The above may be the mechanism by which the FA value in the extension neck position best assesses the value of postoperative recovery in patients with CSM, and the detailed mechanism is unknown.…”
Section: Discussionmentioning
confidence: 95%